Impact of the National Early Warning Score-based sepsis response system on hospital-onset sepsis in a tertiary hospital in South Korea - Hyun, Dong-gon; Lee, Sohyeon; Choi, Sunhui; Son, Jeongsuk; Park, So-Hee; Hong, Sang-Bum; Lim, Chae-Man (Acute and critical care, 2025)
Background: The effectiveness of electronic medical record-based alert systems, response protocols for sepsis diagnosis, and treatment in hospitalized patients remains unclear. This study aimed to determine whether the introduction of an electronic medical record-based sepsis response protocol (SRP) along with a 24/7 operating rapid response system affects the prognosis for patients with hospital-onset sepsis.Methods: In August 2022, a SRP based on the National Early Warning Score was implemented in the electronic medical record system at Asan Medical Center. We retrospectively analyzed patients screened by the detection system for 1 year after the SRP implementation. Patients of the first 6 months (preliminary group) and those of the second 6 months (SRP group) were matched 1:1 based on propensity scores. The primary outcome was 30-day mortality.Results: Of the 608 hospitalized patients screened by the system, 176 were assigned to each group after 1:1 propensity score matching. Patients in the SRP group were significantly more likely to receive blood cultures (58.5%) compared with the preliminary group (45.5%) (P=0.019). The SRP group showed a lower 30-day mortality risk (hazard ratio, 0.56; 95% CI, 0.36–0.86; P=0.017) compared to the preliminary group. A restricted cubic spline curve showed that SRP survival benefit began to manifest after the first 4 months (P=0.036).Conclusions: Alongside an existing rapid response system, the National Early Warning Score-based SRP in the electronic medical record reduced mortality for hospital-onset sepsis within 1 year.